Aymara as a written language and its normalization - Mendoza, José G. (1987)
The term stylistics, according to Ullman, dates back to the romantic period. However, the discipline only became established in its modern form at the beginning of this century. From the beginning, two perspectives are proposed for the study of stylistics: on the one hand, there is interest in the stylistic resources of natural languages, in the expressive artifices that they make available to the user; On the other hand, we can be fundamentally interested in the use of these resources that we can detect in creative authors. Naturally, both aspects of the problem are intimately linked. It is the users of the language themselves who are discovering and proposing new stylistic resources that are later consolidated as the language's own resources. In this work we will deal with the first aspect, that is, with the stylistic resources that Aymara can offer as a language.